Facile and Rapid Synthesis of Ultrafine PtPd Bimetallic Nanoparticles and Their High Performance toward Methanol Electrooxidation. (4th August 2014) - Xia, Tiantian; Shen, Hanrui; Chang, Gang; Zhang, Yuting; Shu, Honghui; Oyama, Munetaka; He, Yunbin
Abstract : Uniform and sub-10 nm size bimetallic PtPd nanoparticles (NPs) have been synthesized via a simple and facile method without using any surfactants at an ambient temperature. As a green and clean reductive agent, ascorbic acid (AA) was employed for the coreduction of K2 PtCl4 and K2 PdCl4 in aqueous solution. The morphology, composition, and structure of PtPd NPs had been characterized by transmission electron microscopy (TEM), field emission high resolution transmission electron microscopy (FE-HRTEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), and X-ray photoelectron spectroscope (XPS). Comparing with both the monometallic Pt and Pd, the as-prepared alloy nanoparticles show superior electrocatalytic activity and better tolerance against poisoning by intermediates generated during methanol electrooxidation, which makes them a promising electrocatalysts for direct methanol fuel cells (DMFCs). Meanwhile, the green and simple approach could be easily extended to the manufacture of bimetallic or trimetallic alloy nanomaterials.